KONSTRIBUSI PENDAPATAN WANITA TERHADAP KETAHANAN PANGAN RUMAH TANGGA PADA AGROEKOSISTEM SAWAH TADAH HUJAN DI KECAMATAN MA’RANG KABUPATEN PANGKEP - Andi Wahida; Ida Rosada; Mais Ilsan (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2019)
Food security is an integrated system consisting of various subsystem. The main subsystem are food availability, food distribution and food consumption. The realization of good security is a synergy of the interactions of the three subsystem. The purpose of this study was to identify female household socioeconomic factors in rainfed lowland agroecosystems in Ma’rang sub-district, Pangkep district, review and analyze the contribution of women’s income to household income, analyze the level of share of women’s household food expenditure in rainfed lowland areas, analyze the level of female household food security in rainfed lowland agroecosystems. This research was conducted in July to September 2018. Sampling was carried out in census, namely 22 households. The results of the study showed that the contribution of women’s income to household income was still very low at 15% of total household income, women’s household food security in rainfed lowland areas is seen from the side of food expenditure, namely 63,64 percent of the share of food expenditure is in the category of food security (≤ 60%) and as much as 36,36 percent of the share of food expenditure in the category is not food resistant (≥ 60 %), and the level of household food security is in the category of food security.